2019
DOI: 10.1136/rapm-2018-000032
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, randomized comparison between 2, 5, and 8 mg of perineural dexamethasone for ultrasound-guided infraclavicular block

Abstract: Background and objectivesThis multicenter, randomized trial compared 2, 5, and 8 mg of perineural dexamethasone for ultrasound-guided infraclavicular brachial plexus block. Our research hypothesis was that all three doses of dexamethasone would result in equivalent durations of motor block (equivalence margin=3.0 hours).MethodsThree hundred and sixty patients undergoing upper limb surgery with ultrasound-guided infraclavicular block were randomly allocated to receive 2, 5, or 8 mg of preservative-free perineur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 26 publications
0
28
1
Order By: Relevance
“…21 Recent studies have shown that perineural high doses of dexamethasone have no advantage, and low doses of dexamethasone are advocated. 22 A recent meta-analysis showed very low quality evidence that there was a ceiling effect of dexamethasone at 4 mg. 23 However, the latest research findings that both intravenous and perineural administered dexamethasone 4 mg has no clinically relevant effect on the duration of sensory block provided by ropivacaine applied to the ulnar nerve in volunteers. 24 In addition, in the current study, we used a higher dose of dexamethasone than other experts have recommended.…”
Section: Discussionmentioning
confidence: 99%
“…21 Recent studies have shown that perineural high doses of dexamethasone have no advantage, and low doses of dexamethasone are advocated. 22 A recent meta-analysis showed very low quality evidence that there was a ceiling effect of dexamethasone at 4 mg. 23 However, the latest research findings that both intravenous and perineural administered dexamethasone 4 mg has no clinically relevant effect on the duration of sensory block provided by ropivacaine applied to the ulnar nerve in volunteers. 24 In addition, in the current study, we used a higher dose of dexamethasone than other experts have recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The current trial was registered at www.clinicaltrials.gov (Study ID: NCT04875039) on 6 May 2021 prior to patient recruitment. The protocol used in the current study was similar to the one employed in our four previous trials investigating perineural dexamethasone or dexmedetomidine for brachial plexus blocks 1 3 13 14…”
Section: Methodsmentioning
confidence: 99%
“…A 6–13 MHz linear array ultrasound (US) transducer (General Electric LOGIC E, General Electric Healthcare, Wauwatosa, Wisconsin, USA) was applied in a sterile fashion in the infraclavicular fossa, medial to the coracoid process, to obtain a short axis view of the axillary artery 1 13 14. A skin weal was raised with 3 mL of lidocaine 1.0%.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous reports have confirmed that dexamethasone and dexmedetomidine prolong the action time following the introduction of local anaesthesia to peripheral nerve block [4][5][6][7]. Combining dexamethasone or dexmedetomidine as a local anaesthetic adjuvant improves block characteristics, whether around the nerve or in the vein [8].…”
Section: Introductionmentioning
confidence: 99%